2022
DOI: 10.1016/j.isci.2021.103596
|View full text |Cite
|
Sign up to set email alerts
|

Cell cycle defects underlie childhood-onset cardiomyopathy associated with Noonan syndrome

Abstract: Summary Childhood-onset myocardial hypertrophy and cardiomyopathic changes are associated with significant morbidity and mortality in early life, particularly in patients with Noonan syndrome, a multisystemic genetic disorder caused by autosomal dominant mutations in genes of the Ras-MAPK pathway. Although the cardiomyopathy associated with Noonan syndrome (NS-CM) shares certain cardiac features with the hypertrophic cardiomyopathy caused by mutations in sarcomeric proteins (HCM), such as pathologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 78 publications
1
17
0
Order By: Relevance
“…Interestingly, no myofibrillar disarray was observed in our cell model. However, the presence of myofibril disarray in NS remains controversial: whereas structural defects were described in RAF1-associated iPSC models, 15,39 we and others did not observe any impact on sarcomere structures or myofibril organization in LZTR1-related, PTPN11-related, and BRAF-related iPSC-CMs, 10,14,16 implying potential genotype-dependent differences in the manifestation of myofibril disassembly in NS.…”
Section: Discussionmentioning
confidence: 88%
“…Interestingly, no myofibrillar disarray was observed in our cell model. However, the presence of myofibril disarray in NS remains controversial: whereas structural defects were described in RAF1-associated iPSC models, 15,39 we and others did not observe any impact on sarcomere structures or myofibril organization in LZTR1-related, PTPN11-related, and BRAF-related iPSC-CMs, 10,14,16 implying potential genotype-dependent differences in the manifestation of myofibril disassembly in NS.…”
Section: Discussionmentioning
confidence: 88%
“…6i). We recently reported that hiPSC-derived CMs from this individual displayed cell cycle defects, leading to hyperproliferation rather than a classical hypertrophic phenotype when cultured in 2D 60 . The same was observed in individual-specific epicardioids; they did not have larger CMs than healthy controls and did not upregulate hypertrophy markers but showed increased CM proliferation across the myocardial layers (Supplementary Fig.…”
Section: Articlementioning
confidence: 88%
“…When differentiated into cardiomyocytes these cells show a phenotype consistent with cardiac hypertrophy, with larger surface area compared to wt-iPSCs and HES2 cells, increased sarcomere assembly and nuclear localization of NFATc4. In contrast, both cardiac tissue from NS patients with CRAF and SHP2 variants, and iPSCs with SHP2-N308S variant, display cellular hyperplasia, rather than hypertrophy, which is presumably due to the increased cell cycle progression (Meier et al, 2021). However, hypertrophic phenotypes are observed in cardiomyocytes differentiated from NS-derived iPSCs with CRAF mutations (Jaffré et al, 2019;Nakhaei-Rad et al, 2022).…”
Section: Induced Pluripotent Stem Cellsmentioning
confidence: 89%
“…As human model for NS and NSML, patient derived iPSCs containing SHP2 variants, are used to study cardiac, neuronal and hematopoietic defects (Carvajal-Vergara et al, 2010;Hamada et al, 2020;Li et al, 2019;Meier et al, 2021;Mulero-Navarro et al, 2015;Pearson et al, 2020). The first iPSCs with SHP2 variants were derived more than a decade ago from skin fibroblasts of two NSML patients carrying the SHP2-T468M mutation (Carvajal-Vergara et al, 2010).…”
Section: Induced Pluripotent Stem Cellsmentioning
confidence: 99%